2021
DOI: 10.3390/ijms22115775
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages/Microglia in the Glioblastoma Tumor Microenvironment

Abstract: The complex interaction between glioblastoma and its microenvironment has been recognized for decades. Among various immune profiles, the major population is tumor-associated macrophage, with microglia as its localized homolog. The present definition of such myeloid cells is based on a series of cell markers. These good sentinel cells experience significant changes, facilitating glioblastoma development and protecting it from therapeutic treatments. Huge, complicated mechanisms are involved during the overall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 119 publications
(129 reference statements)
1
29
0
1
Order By: Relevance
“… 32 Moreover, the total number of microglia cells does not vary with the grade of malignancy, but macrophages enrich in high-grade gliomas. 33 Our previous study also confirmed that macrophage, but not microglia, was identified with prognostic significance in glioma progression. 3 These results strengthened the important role of macrophages in glioma progression.…”
Section: Discussionsupporting
confidence: 76%
“… 32 Moreover, the total number of microglia cells does not vary with the grade of malignancy, but macrophages enrich in high-grade gliomas. 33 Our previous study also confirmed that macrophage, but not microglia, was identified with prognostic significance in glioma progression. 3 These results strengthened the important role of macrophages in glioma progression.…”
Section: Discussionsupporting
confidence: 76%
“…Clinical studies have shown that there is a large number of microglia in GBM tissue [ 54 , 55 ]. GBM tissue promotes the polarization of microglia toward anti-inflammatory M2 type [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…GAMs represent an important component of the glioma microenvironment ( 54 ) constituting the main proportion of infiltrating cells in adult and pediatric HGGs (i.e., glioblastoma and DIPG) ( 55 , 56 ). Inside the tumor, GAMs usually acquire a specific phenotype of activation that favors tumor growth, angiogenesis and promotes the invasion of normal brain parenchyma.…”
Section: Tumor Microenvironment In Adult and Pediatric High-grade Gliomamentioning
confidence: 99%